2022
DOI: 10.1021/acssuschemeng.2c00518
|View full text |Cite
|
Sign up to set email alerts
|

Power Generation by Flat-Tube Solid Oxide Fuel Cells with Enhanced Internal Reforming of Methanol

Abstract: Methanol is a promising fuel for solid oxide fuel cells (SOFCs) because of its low cost and ease of storage and transportation. In this work, the performance and long-term durability of direct methanol flat-tube SOFCs are investigated under different steam/carbon (S/C) ratios. It is confirmed that the S/C ratio exhibits little influence on cell performance but strongly affects long-term stability. The cell is discharged stably under high S/C ratios of 1.5 and 1.2, while it fails abruptly under a low S/C ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…From Fig. 9b, it can be observed that the methanol conversion rate decreases with the addition of steam, consistent with the experimental results of Sang et al 36 Due to the dilution effect of steam, although adding steam leads to a decrease in the MDR, it can be seen from Fig. 9b that the methanol concentration at the outlet decreases with the increase in the proportion of steam.…”
Section: Resultssupporting
confidence: 88%
“…From Fig. 9b, it can be observed that the methanol conversion rate decreases with the addition of steam, consistent with the experimental results of Sang et al 36 Due to the dilution effect of steam, although adding steam leads to a decrease in the MDR, it can be seen from Fig. 9b that the methanol concentration at the outlet decreases with the increase in the proportion of steam.…”
Section: Resultssupporting
confidence: 88%
“…Initially, a dendritic pore channel anode design was introduced, expected to improve fuel diffusion and distribution on the catalyst surface, as well as reaction efficiency within the cell, thereby diminishing the likelihood of carbon deposition . Furthermore, co-reforming fuel with steam , is employed to augment the cell’s electrochemical reaction process. The cell is designed for operation at a stable output current, aiming to reduce carbon formation.…”
Section: Introductionmentioning
confidence: 99%
“…SOFCs are used to efficiently produce electricity using a fuel such as hydrogen (H 2 ). The high operating temperature of SOFCs (500 °C-1,000 °C) allows them to operate using a variety of fuels, such as carbon monoxide (CO), methane (CH 4 ), methanol (CH 3 OH), and ammonia (NH 3 ) (Donazzi et al, 2016;Kishimoto et al, 2020;Fan et al, 2022;Sang et al, 2022). Conversely, SOECs are used to produce fuels like H 2 and CO, starting from water (H 2 O), carbon dioxide (CO 2 ), and an electricity supply.…”
Section: Introductionmentioning
confidence: 99%